Semen Quality, Fertility and Testicular Histology of Rabbit Bucks Orally Administrated with Ethanolic Grape Seed Extract - El-Ratel, Ibrahim T.; Zaghloul, Helmy K.; Shamiah, Sherif M. (Pakistan Journal of Nutrition, 2019)
Objective: Effect of daily oral administration with ethanolic grape seed extract (EGSE) as enhancing factors on reproductive performance of APRI line rabbit bucks was investigated in this study. Materials and Methods: Total of 18 rabbit bucks (6 in each group) were treated with 3 mL distilled water containing 0 as control group, 75 and 125 mg kg–1 live body weight (LBW) from EGSE, for 28 days as a treatment period. Semen was collected twice a week for 8 wks as a collection period, then the average of physical semen characteristics were calculated for three semen collection intervals. Aspartate (AST) and alanine (ALT) transaminases activity, total antioxidant capacity (TAC) and testosterone concentrations were determined in blood serum. Results: Administrated with 125 mg EGSE kg–1 LBW showed a significant improved (p<0.05) testicular weights, semen quality (progressive motility, livability, abnormality, acrosomal damage, cell concentration and outputs/ejaculate of spermatozoa), except semen volume and by advancing semen collection interval, testosterone and TAC concentrations, while, ALT activity (p<0.05) reduced compared with the control group. Conclusion: Practically, using natural antioxidant such as grape seed extract for 28 days, may increase the antioxidative capacity of testicular tissues of rabbit bucks to improve semen quality and reproductive traits.